Embolization of variant hepatic arteries in patients undergoing percutaneous hepatic perfusion for unresectable liver metastases from ocular melanoma - T. Susanna Meijer; Lioe-Fee de Geus-Oei; Christian H. Martini; Fred G. J. Tijl; M. Elske Sitsen; Arian R. van Erkel; Rutger W. van der Meer; Ellen Kapiteijn; Alexander L. Vahrmeijer; Mark C. Burgmans (Diagnostic and Interventional Radiology, 2019)

(untitled)
PURPOSEIn patients undergoing percutaneous liver perfusion with melphalan (M-PHP), the presence of variant hepatic arteries (HAs) may require catheter repositioning and thus prolong procedure time. Coil-embolization of variant HAs may enable M-PHP with a single catheter position as occlusion of variant HAs results in redistribution of flow through preexisting intrahepatic arterial collaterals. We aimed to evaluate whether redistribution of flow has any negative effect on therapeutic response in ocular melanoma patients undergoing M-PHP.METHODSWe retrospectively analyzed pretreatment angiograms in all 32 patients that underwent M-PHP between January 2014 and March 2017 for unresectable liver metastases from ocular melanoma. Patients that underwent embolization of a variant left HA (LHA) or middle HA (MHA) during pretreatment angiography followed by at least one technically successful M-PHP were included for further analysis. Redistribution of arterial flow was evaluated on angiography and cone-beam computed tomography (CBCT) images. In each patient, tumor response in liver segments with redistributed blood flow was evaluated using RECIST 1.1 and mRECIST, and then compared with tumor response in segments without flow redistribution. Follow-up scans were reviewed to evaluate progression of liver metastases.RESULTSA total of 12 patients were included. Replaced LHA embolization resulted in redistribution of flow to segment(s) 2 (n=3), 2 and 3 (n=5), and 2, 3 and 4 (n=2). MHA embolization resulted in redistribution of flow to segment 4 (n=2). Successful redistribution was confirmed by angiography and/or CBCT in all patients. Tumor response was similar for redistributed and non-redistributed liver segments in 8 out of 9 patients (89%) according to RECIST 1.1, and in 7 out of 8 patients (88%) according to mRECIST. In three patients, tumor response was not evaluable according to RECIST 1.1 or mRECIST as metastases were too small to be categorized as target lesions (n=1), or target lesions were confined to non-redistributed segments (n=2). In one patient, tumor response was not evaluable according to mRECIST as target lesions in the redistributed segments were hypovascular. After a median follow-up time of 17.1 months (range, 9.1–38.5 months), hepatic progression was seen in 9 out of 12 patients with a median time to progression of 9.9 months (range, 2.5–17.7 months). Progression of liver metastases was never seen only in the redistributed liver segments.CONCLUSIONFlow redistribution in liver segments by coil-embolization of variant HAs is a feasible technique that does not seem to compromise tumor response in patients undergoing M-PHP.